2023
DOI: 10.3390/life13020466
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Silver Nanoparticles in the Diagnosis and Treatment of Cancer: Are There Any Perspectives for the Future?

Abstract: Cancer is a fatal disease with a complex pathophysiology. Lack of specificity and cytotoxicity, as well as the multidrug resistance of traditional cancer chemotherapy, are the most common limitations that often cause treatment failure. Thus, in recent years, significant efforts have concentrated on the development of a modernistic field called nano-oncology, which provides the possibility of using nanoparticles (NPs) with the aim to detect, target, and treat cancer diseases. In comparison with conventional ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 259 publications
1
25
0
Order By: Relevance
“…Cell death expanded with expanding groupings of AgNPs and hindrance of half-cell passing requires a little portion of AgNPs. It has been accounted for that the AgNPs treatment causes harm to the mitochondrial film and delivers cytochrome c, which is a basic angle showing apoptosis in cells animated by cytoplasm 69 . Here, our outcomes demonstrated that the formulated te-AgNPs, gr-AgNPs, and am-AgNPs effectively inhibited growth and induced apoptosis in the breast cancer MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death expanded with expanding groupings of AgNPs and hindrance of half-cell passing requires a little portion of AgNPs. It has been accounted for that the AgNPs treatment causes harm to the mitochondrial film and delivers cytochrome c, which is a basic angle showing apoptosis in cells animated by cytoplasm 69 . Here, our outcomes demonstrated that the formulated te-AgNPs, gr-AgNPs, and am-AgNPs effectively inhibited growth and induced apoptosis in the breast cancer MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hetta et al [96] found out that at the lowest subinhibitory concentration, (AgNPs) suppressed the expression of specific virulence and biofilm-related genes (kpsMII, afa/draBC, Bap, ompA, and csuA/B), resulting in a decrease in the biofilm concentration of A. baumannii. AgNPs were also shown to be a promising agent for inhibiting cancer cell growth through multiple mechanisms [97]. A study using silica NPs found that it can specifically target Acinetobacter biofilms while preserving the viability of normal cells; viability rates ranged from 61% to 73%.…”
Section: Nanoparticles (Nps)mentioning
confidence: 99%
“…Currently, extensive research is being conducted on silver nanoparticles (AgNPs) due to their wide range of potential applications. AgNPs can be used in various materials, including optical sensors [ 2 ], electrical batteries [ 3 ], supercapacitors [ 4 ], nanoceramics [ 5 ], flame retardants [ 6 ], biosensors [ 7 ], drug delivery vehicles [ 8 ], catalysts [ 9 ], and as antimicrobial, antioxidant, anti-inflammatory, and anticancer agents [ 10 , 11 , 12 ]. Due to their antibacterial properties, AgNPs have found widespread use in various applications, including dental implants, surgical devices, bone and tissue engineering applications, and other biomedical devices [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%